The Influence of Digital Transformation and Emotional Intelligence (EI) on Performance - Dwi Mahendra, Nanda (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The Effect of Digital Transformation and Emotional Intelligence (EI) on Performance is a scientific article on literature study within the scope of Management Information Systems. The aim of this article is to build a hypothesis of the influence between variables that will be used in further research. Object research in online libraries, Google Scholar, Mendeley and other academic online media. Research methods with libraries risearch sourced from e-books and open access e-journals. Qualitative descriptive analysis. Results of this article: 1) Digital Transformation influence on performance. 2) Emotional Intelligence (EI) influences performance